Boronic Acid Homopolymers as Effective Polycations for Sugar-Responsive Layer-by-Layer Assemblies - Bruen, Danielle; Campos, Paula P. [UNESP]; Ferreira, Marystela; Diamond, Dermot; Delaney, Colm; Florea, Larisa (Amer Chemical Soc, 2019)
Owed to their reversible diol-binding ability, phenylboronic acid (BA) derivatives have gained considerable interest for the development of saccharide sensors and drug delivery systems. In particular, BA-containing polymers have been used for the realization of sugar-responsive layer-by-layer (LbL) films. Herein, a LbL system based on cationic BA-homopolymers (PBA) is presented, and its subsequent sugar-induced disassembly is described. The BA-linear polymers (PBA) were intercalated with poly(vinylsulfonic acid, sodium salt) to form (PBA/PVS)(n) film assemblies. Different orientations of the boronic acid substituent (ortho-, meta-, and para-) in the PBA polymer were investigated for their influence on the LbL assembly. The rate of disassembly in the presence of glucose or fructose was analyzed by UV-vis spectroscopy. Additionally, the PVS component was replaced with an anionic fluorophore, pyranine (PYR), which allowed the assembly and disassembly to be monitored by fluorescence.
Keywords: layer-by-layer; boronic acid; fluorescence; fructose; pyranine; stimuli-responsive